Congenital hyperinsulinism in the Ukraine: a 10-year national study - Evgenia Globa; Henrik Thybo Christesen; Michael Bau Mortensen; Jayne A. L. Houghton; Anne Lerberg Nielsen; Sönke Detlefsen; Sarah E. Flanagan (Frontiers in Endocrinology)
IntroductionCongenital Hyperinsulinism (CHI) has not been previously studied in Ukraine. We therefore aimed to elucidate the genetics, clinical phenotype, histological subtype, treatment and long-term outcomes of Ukrainian patients with CHI.MethodsForty-one patients with CHI were recruited to the Ukrainian national registry between the years 2014-2023. Genetic testing (n=40), 18F-fluorodihydroxyphenylalanin and 68Ga-DOTANOC PET/CT imaging followed by surgical treatment and subsequent histological analysis (n=19) was performed through international collaboration.ResultsPathogenic variants were identified in 19/22 (86.3%) individuals with persistent CHI (p-CHI) and 8/18 (44.4%) with early remission CHI (er-CHI). Pathogenic variants in the K-ATP channel genes were the only identified genetic cause of p-CHI (ABCC8 (n=17) and KCNJ11 (n=2)) with greater genetic heterogeneity observed in those with er-CHI (ABCC8 (n=3), KMT2D (Kabuki Syndrome, n=1), Beckwith-Wiedemann syndrome (n=2) and INSR (Donohue syndrome (n=2)). Histological analysis performed on 19 children with persistent CHI confirmed focal disease in 14 (73.7%), diffuse disease in two (10.5%) and atypical histology in three (15.8%). After surgery, complete recovery was observed in all 14 with focal disease, while relapse occurred in three patients with diffuse or atypical histology.ConclusionA genetic diagnosis was achieved for 67.5% (27/40) of the cohort with a higher pick-up rate observed in those with p-CHI. The genetics and imaging studies enabled subtype-targeted treatment with surgical cure achieved in all individuals with focal disease.